Pharmacogenetics of the response to ββ2 agonist drugs: a systematic overview of the field. (August 2007) - Contopoulos-Ioannidis, Despina G; Kouri, Ioanna; Ioannidis, John PA
The response to ββ2-agonist treatment shows large repeatability within individuals and may thus be determined by genetic influences. Here we present a systematic overview of the available genetic association and linkage data for ββ2-agonist treatment response. Systematic searches identified 66 eligible articles, as of March 2007, pertaining either to B2AR gene polymorphisms and short-acting or long-acting ββ2-agonists or to another 29  different genes. We systematize these study results according to gene, agent and type of outcomes addressed. The systematic review highlights major challenges in the field, including extreme multiplicity of analyses; lack of consensus for main phenotypes of interest; typically small sample sizes; and poor replicability of the proposed genetic variants. Future studies will benefit from standardization of analyses and outcomes, hypothesis-free genome-wide association testing platforms, potentially additional fine mapping around new discovered variants, and large-scale collaborative studies with prospective plans for replication among several teams, with transparent public recording of all data.